2013
DOI: 10.1155/2013/759483
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B Prevents Arsenic Trioxide-Induced CardiotoxicityIn Vivoand Enhances Its Anticancer ActivityIn Vitro

Abstract: Clinical attempts to reduce the cardiotoxicity of arsenic trioxide (ATO) without compromising its anticancer activities remain to be an unresolved issue. In this study, we determined whether Sal B can protect against ATO-induced cardiac toxicity in vivo and increase the toxicity of ATO toward cancer cells. Combination treatment of Sal B and ATO was investigated using BALB/c mice and human hepatoma (HepG2) cells and human cervical cancer (HeLa) cells. The results showed that the combination treatment significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Our results also implicated ER stress-associated apoptosis inhibition in the Sal B cardioprotective mechanism. Combined with our previous report [ 19 , 20 ], our findings demonstrated that Sal B protects against ATO-induced cardiotoxicity not only through its anti-oxidative and anti-apoptotic capacities, but also by modulating calcium homeostasis and suppressing ER stress.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results also implicated ER stress-associated apoptosis inhibition in the Sal B cardioprotective mechanism. Combined with our previous report [ 19 , 20 ], our findings demonstrated that Sal B protects against ATO-induced cardiotoxicity not only through its anti-oxidative and anti-apoptotic capacities, but also by modulating calcium homeostasis and suppressing ER stress.…”
Section: Discussionsupporting
confidence: 87%
“…All animal care procedures and interventions were performed in accordance with the Guidelines and Policies for Animal Surgery provided by the Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, China, and were approved by the Institutional Animal Use and Care Committee (registration number: #IMPLAD2015090216). Experimental protocols were previously described [ 20 ]. In brief, rats were randomly divided into four groups (n=15/group): (I) the control group (10 mL/kg saline), (II) Sal B-treated group (2 mg/kg Sal B), (III) ATO-treated group (1 mg/kg ATO), and (IV) ATO + Sal B group (2 mg/kg Sal B 1 h before ATO administration).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its role in reversing tumor MDR has attracted increasing attention (10,11). In the present study, SalB was used to treat the MDR colorectal cancer cell line HCT-8/VCR, and explore its effect on drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Many results showed that ginsenoside 20(S)-Rg 3 might provide neuroprotection against the cerebral ischemia-induced injury in rat brain through reducing lipid peroxides, scavenging free radicals and improving the energy metabolism [5]; ginsenoside 20(R)-Rg 3 could attenuate the neuronal apoptosis caused by cerebral ischemiareperfusion injury [6]; ginsenoside Rk 3 had been reported to exert cardio protective effects against hypoxia/reoxygenation (H/R) injury [7]; ginsenosides 20(S)-Rg 3 and 20(S)-Rh 2 had the potential to induce cell detachment and inhibit the proliferation of prostate cancer cells [8]; ginsenoside Rg 5 could induce apoptosis and DNA damage in human cervical cancer cells [9]; ginsenoside Rk 1 had the capability to inhibit telomerase activity and induce apoptosis in human hepatocellular carcinoma cells [10]; and ginsenoside F 4 and ginsenoside Rg 6 had the ability of inhibitory and apoptosis-inducing effect on (GF4) human lymphocytoma Jurkat (JK) cell [11,12]. Therefore, the rare ginsenosides plays an important role in the function of Xue-Sai-Tong injection.…”
Section: Introductionmentioning
confidence: 99%